Kontribusi Planned Happenstance Skills terhadap Perilaku Eksplorasi Karier Siswa Sekolah Menengah Kejuruan: Peran Mediasi Career Decision Self-Efficacy - Ramdhan, Subhanallah; Salim, Rose Mini Agoes (Jurnal Kajian Bimbingan dan Konseling, 2020)
Career exploration is the acquisition of career information that results in the formation of career maturity. This study aims to explain the role of internal factors that drive career exploration behavior. Specifically, the study examines the role of career decision self-efficacy in mediating the effect of planned happenstance skills on career exploration behavior. The study applied correlational design with regression analysis. 414 male and 394 female students from vocational high schools in Jakarta were chosen purposively to participate in the study. The Career Exploration Survey, The Planned Happenstance Skill Inventory, and The Career Decision Self-Efficacy Scale-Short Form were used to collect research data. The results show that the effect of planned happenstance skills on student career exploration behavior was partially mediated by career decision self-efficacy. This indicates that the development of the ability to take advantage of certain events can form career related behaviors. Based on the results, it is recommended for school counselors to train students with planned happenstance skills while conducting career counseling in order to develop their career readiness optimally